PENGARUH ANTI RETRO VIRAL (ARV) TERHADAP KADAR CD4, SGOT DAN SGPT PADA PASIEN HUMAN IMMUNODEFICIENCY VIRUS (HIV) - Yusuf, Rahmi Novita; Ibrahim, Ibrahim; Sari, Indah Komala; Zamsri, Yuliani (STIKES Syedza Saintika Padang, 2024)
Human Immunodeficiency Vyrus (HIV) is a virus that attacks and damages the human immune system which causes a decrease in CD4 levels in the body. CD4 is a marker or markers that are on lymphocytes. Handling HIV is carried out with Anti Retro Viral (ARV) therapy which aims to suppress viral replication. The use of ARVs consisting of several drugs requires special attention, one of which is monitoring liver function by examining SGOT and SGPT. The purpose of this study was to determine the effect of ARVs on CD4, SGOT and SGPT levels in HIV patients at RSUP Dr. M. Djamil Padang. This research is a type of analytical observation research with a retrospective design. The population in this study were 115 HIV patients with a sample of 89 people. Analysis of research data was carried out using the Paired Sample T-test. It was obtained that the average CD4 level of HIV patients before ARV was 197.9 cells/mm3 with a minimum score of 106 cells/mm3 and a maximum score of 340 cells/mm3. the average score of CD4 levels in HIV patients after ARV is 247.3 cells/mm3 with a minimum score of 145 cells/mm3 and a maximum score of 456 cells/mm3. the average score of SGOT levels in HIV patients before ARVs was 24.84 U/L with a minimum score of 14 U/L and a maximum score of 40 U/L. the average score of SGOT levels in HIV patients after ARV is 29.61 U/L with a minimum score of 15 U/L and a maximum score of 45 U/L. the average SGPT level of HIV patients before ARV was 24.84 U/L with a minimum value of 10 U/L and a maximum score of 47 U/L and the average SGPT level score of HIV patients after ARV was 27.70 U/L with minimum score of 11 U/L and maximum score of 49 U/L. The results of the Paired Sample T-Test for the effect of ARVs on CD4, SGOT and SGPT levels in HIV patients were p value = 0.000 (a = 0.05) meaning that pv is less than a, which means that statistically Ha is accepted and Ho is rejected. The conclusion of the research results is that there is an effect of ARVs on CD4, SGOT and SGPT levels in HIV patients at RSUP Dr. M. Djamil Padang. Keywords : HIV, Anti Retro Viral Therapy (ARV)